Variability in magnesium content in Arctic echinoderm skeletons. (August 2017) - Iglikowska, A.; Najorka, J.; Voronkov, A.; Chełchowski, M.; Kukliński, P.
Abstract: In this study, 235 measurements of magnesium concentration in echinoderm's skeletons were compiled, including 30 species and 216 specimens collected from northern and western Barents Sea. We aimed to reveal the scale of Mg variation in the skeletons of Arctic echinoderms. Furthermore, we attempted to examine whether the Mg concentration in echinoderm skeletons is determined primarily by biological factors or is a passive result of environmental influences. We found that the Mg concentration in echinoderm skeletons was characteristic for particular echinoderm classes or was even species-specific. The highest Mg contents were observed in asteroids, followed by ophiuroids, crinoids, and holothuroids, with the lowest values in echinoids. These results strongly imply that biological factors play an important role in controlling the incorporation of Mg into the skeletons of the studied individuals. Highlights: The skeleton of echinoderms consists of calcite with high content of MgCO3 . Mg contents in skeletons were characteristic for particular echinoderm classes. The highest Mg contents were noted in asteroids and the lowest in echinoids. Incorporation of Mg into the skeletons is mostly controlled biologically. Arctic species show lower Mg contents comparing to those from lower latitudes.